Eficacia de la poligelína 3.5% vs cloruro de sodio 9‰ para prevenir la hipotensión materna en gestantes sometidas a césarea bajo anestesia espinal en el Hospital Belén de Trujillo, 2018 - Surichaqui Quispe, Hernán Richard (2019)
Introduction: Spinal anesthesia is one of the most used for elective cesarean because of its ease and being a reliable technique; but one of the side effects is arterial hypotension, which causes adverse effects for both the mother and the fetus due to the neuraxial block. Therefore, the first line to prevent and treat this problem is the administration of intravenous fluids to increase blood volume. Objective: To compare the incidence of maternal hypotension produced by spinal block using Sodium Chloride 9 ‰ vs Polygeline 3.5% in elective cesareans. Method: This study corresponds to a prospective design, simple blind experimental regimen and free regimen. Conclusion: Poligeline 3.5% decreases the incidence of maternal hypotension in less than or equal to Sodium Chloride 9 ‰ in pregnant women undergoing cesarean section under spinal anesthesia